1981
DOI: 10.1002/jsscb.380170103
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages and methylthio groups in lymphocyte proliferation

Abstract: Macrophages are shown to replace methylthio disulfides in supporting in vitro proliferation of three cell lines previously characterized as methylthio-dependent. Macrophages have the capacity to generate methylthio groups from methylthioadenosine. It is hypothesized that macrophages stimulate cell proliferation both in normal immune systems and in certain cancers by providing an abundance of methylthio groups. Fetal calf serum is shown to contain methylthio groups. It appears that, in cell cultures containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…Sera other than fetal calf serum are ineffective with the second group [18]. Cystine is active at 1 mM in the presence of a pyridoxal catalyst [17].…”
Section: Sulfur As a Regulatory Agentmentioning
confidence: 99%
“…Sera other than fetal calf serum are ineffective with the second group [18]. Cystine is active at 1 mM in the presence of a pyridoxal catalyst [17].…”
Section: Sulfur As a Regulatory Agentmentioning
confidence: 99%
“…In the first, it is a byproduct of polyamine synthesis (36), which also yields methylthioadenosine. This may be cleaved to methylthioribose 1-phosphate and adenine by a specific nucleoside phosphorylase (37 (44,(46)(47)(48), by certain disulfides (42), by CH3S-group donors (49), and by feeder cells (46,50). In the presence of sulfhydryl compounds, horse, bovine, calf, and newborn calf sera cannot replace fetal calf serum, and growth factor activity in the latter is lost after dialysis against glutathione (50).…”
Section: Resultsmentioning
confidence: 99%
“…This may be cleaved to methylthioribose 1-phosphate and adenine by a specific nucleoside phosphorylase (37 (44,(46)(47)(48), by certain disulfides (42), by CH3S-group donors (49), and by feeder cells (46,50). In the presence of sulfhydryl compounds, horse, bovine, calf, and newborn calf sera cannot replace fetal calf serum, and growth factor activity in the latter is lost after dialysis against glutathione (50). CH3S groups have been demonstrated in fetal calf serum protein, suggesting that these could be its uniquely stable growth factor (50).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This pathway can generate methylthio groups via ketomethylthiobutyrate (see Fig. The essential growth factor was, at first, provided by fetal calf serum plus a sulfhydryl compound [94]; later it was shown that treatment of fetal calf serum with R-SH caused the release of CH 3 -SH which was identified by GC-MS [95]. These findings sugggest that methylthio groups have an essential function in all cells.…”
Section: Teleology: Why Should Mthf:hmt Make Isomethionine?mentioning
confidence: 99%